Development of a low-emissions solid waste management strategy for East Jakarta, Indonesia - Sekarsari Nindi; Kristanto Gabriel Andari; Dahlan Astryd Viandila (E3S Web of Conferences, 2023)
The relationship between municipal solid waste management and anthropogenic greenhouse gas (GHG) emissions has attracted significant attention worldwide. Solid Waste Management (SWM) systems contribute to GHG emissions at all stages of their management. This study aimed to provide an overview of the SWM system in East Jakarta and present guidelines for developing the right strategy for low-emissions SWM using three scenarios. GHG emissions were calculated for 2030 projections using the Emissions Quantification Tool (EQT) for Estimating Short-Lived Climate Pollutants (SLCPs) and Other GHG from the Waste Sector 2018 Version II, which was developed by the Institute for Global Environmental Strategies (IGES). Scenario 1, with 70% of waste entering the landfill, emitted 426.00 thousand tons CO2-eq/year. Meanwhile, scenarios 2 and 3, which involved biological and thermal processing, respectively, emitted -161.17 and -133.48 thousand tons CO2-eq/year. The differences in GHG emissions values between these scenarios were due to the type of processing process and processing capacity of each solid waste treatment technology. Furthermore, materials and energy recovery from several solid waste treatment technologies can provide GHG avoidance, resulting in a reduction of total emissions from SWM systems.